2011
DOI: 10.4319/lo.2011.56.4.1179
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of chitinase activity and uptake of hydrolysis products in freshwater bacterioplankton

Abstract: We investigated to what extent chitinolytic bacteria subsidize bacterial populations that do not produce chitinolytic enzymes but still use the products of chitin hydrolysis. Applying single-cell techniques to untreated and chitin-enriched lake water, we show that the number of planktonic cells taking up chitin hydrolysis products by far exceeds the number of cells expressing chitinases. Flavobacteria, Actinobacteria, and specifically members of the abundant and ubiquitous freshwater Ac1 cluster of the Actinob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 36 publications
10
69
2
Order By: Relevance
“…Salcher et al (2013) also found that acI was active in leucine uptake. Some MAR-FISH studies have suggested that another nitrogen-rich compound, NAG may be an important acI substrate (Beier and Bertilsson, 2011;Eckert et al, 2012Eckert et al, , 2013. However, we could not identify machinery to support the ability to take up and incorporate this substance.…”
Section: Ecogenomics Of the Aci Lineagecontrasting
confidence: 39%
See 1 more Smart Citation
“…Salcher et al (2013) also found that acI was active in leucine uptake. Some MAR-FISH studies have suggested that another nitrogen-rich compound, NAG may be an important acI substrate (Beier and Bertilsson, 2011;Eckert et al, 2012Eckert et al, , 2013. However, we could not identify machinery to support the ability to take up and incorporate this substance.…”
Section: Ecogenomics Of the Aci Lineagecontrasting
confidence: 39%
“…These studies have shown that acI members can take up glucose (Buck et al, 2009), leucine (Buck et al, 2009;Perez et al, 2010;Salcher et al, 2010;Eckert et al, 2012), acetate (Buck et al, 2009), thymidine (Perez et al, 2010), N-acetylglucosamine (NAG) (Beier and Bertilsson, 2011;Eckert et al, 2012) and di-NAG (Beier and Bertilsson, 2011;Eckert et al, 2012;Tada and Grossart, 2014). A recent MAR-FISH study performed on fall samples from Lake Zü rich in Switzerland showed that acI bacteria consumed an amino acid mixture as well (Salcher et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Particle-associated microbes have the advantage of benefiting directly from the soluble oligomers produced by chitin hydrolysis. However, planktonic bacteria can also profit from chitin hydrolysis products, which has been shown recently for members of planktonic freshwater Actinobacteria (5).…”
Section: Discussionmentioning
confidence: 99%
“…Marine and brackish Flavobacteriales preferably incorporated high-molecular-weight DOM such as proteins or chitin (Cottrell and Kirchman, 2000). Freshwater Flavobacteriales were repeatedly reported to be only marginally involved in AA turnover (Pérez and Sommaruga, 2006;Salcher et al, 2010), but could be experimentally enriched with chitin (Beier and Bertilsson, 2011) and incorporated the mono-and dimeric chitin units N-acetyl-glucosamine and di-N-acetyl-glucosamine (Beier and Bertilsson, 2011;Eckert et al, 2012). The freshwater bacterium Flavobacterium johnsoniae strain A3 preferentially utilized oligopeptides and proteins over individual AAs and had a higher specific affinity for di-and polysaccharides than for Fru (Sack et al, 2011).…”
Section: Differences Within Bacteroidetesmentioning
confidence: 99%